Analysis of Phonological Errors in Reading Essays of Class III Students of Sempu 1 Public Elementary School - Ainun Nurin, Amirah; Widjojoko, Widjojoko; Wardana, Deni (PT Literasi Nusantara Publisher, 2022)
In the world of education, Indonesian has a very important role. To develop our communication skills, we must learn Indonesian language lessons, so that we can express thoughts and feelings through reading and writing activities. Speaking is a language activity carried out by humans in language life after listening. For someone who has the ability to speak, it is easier to convey ideas or ideas to others. Analysis of language errors is a language learning activity that deviates from the rules of the Indonesian language. Through the analysis of language errors, it can be revealed that many things are related to language errors by language learners, namely the background of the causes of errors and types of errors. The purpose of analyzing language errors is to improve and increase the success of learning and teaching language. This study discusses the analysis of phonological errors in reading essays by third grade students of SDN Sempu 1. The purpose of this study is to find out phonological errors in reading student essays and to obtain predictions of error-prone readings of students' essays through the media of picture series for class students. III. This research uses a qualitative descriptive research type. The source of the data used is a story essay written by grade III students. The data collection technique used in this study is a data collection technique using documentation studies. The data analysis technique uses error analysis techniques according to Tarigan, namely collecting data, identifying data, ranking errors, explaining errors, and estimating error-prone locations. The results of this study found that in reading the essays made by grade III students there were still many language errors at the phonological level in word selection, word addition, and word subtraction.